The role of cervical vertebrae maturation in defining the chronological age of Down syndrome children - Aggiani Dewi Rahmawati; Iwan Ahmad; Arlette Suzy Setyawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: The difficulty of determining chronological age is increased in individuals with conditions that may affect normal development. Some systemic conditions in children, for example Down syndrome, may cause abnormal physiological maturation. Skeletal and dental age are considered the most apt physiological age indicators in determining chronological age. Purpose: This study aimed to compare and analyze the relationship between two developmental parameters (dental history and skeletal age) as indicators of the chronological age of children with Down syndrome. Methods: The study design was cross-sectional with a paired t-test to analyze the differences in chronological and dental age of the samples. The radiograph selection was based on purposive sampling. The study material consisted of 30 panoramic radiographs and lateral cephalometrics of 6-14 years old children with Down syndrome and those experiencing normal development (control group) divided into two groups of 15 subjects who attended the Pediatric Dentistry Polyclinic, RSGM, Universitas Padjadjaran. Statistical analysis employed a t-test to determine the difference between chronological and dental age, while a Spearman rank correlation was used to evaluate the correlation between dental and skeletal age. Results: The results showed there to be no statistical difference between chronological and dental age, where p > 0.05, but a significant relationship between dental and skeletal age in children diagnosed with Down syndrome, where p = 0.05. Conclusion: It is concluded that dental age identified by means of the Nolla method is closer to chronological age than skeletal age using the cervical vertebrae maturation method.